2016
DOI: 10.1051/matecconf/20164008002
|View full text |Cite
|
Sign up to set email alerts
|

Controls of Hydraulic Wind Turbine

Abstract: Abstract. In this paper a hydraulic wind turbine generator system was proposed based on analysis the current wind turbines technologies. The construction and principles were introduced. The mathematical model was verified using MATLAB and AMsim. A displacement closed loop of swash plate of motor and a speed closed loop of generator were setup, a PID control is introduced to maintain a constant speed and fixed frequency at wind turbine generator. Simulation and experiment demonstrated that the system can connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The wind energy is converted to mechanical energy by Rotor. The rotor speed ( r  )is a function of the Rotor torque ( a T )and hydraulic pump torque( r T ) and based on the Newton second law, it can be written as [13]:…”
Section: Figure 2: Desalination Wind Turbine Model For Brackish Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The wind energy is converted to mechanical energy by Rotor. The rotor speed ( r  )is a function of the Rotor torque ( a T )and hydraulic pump torque( r T ) and based on the Newton second law, it can be written as [13]:…”
Section: Figure 2: Desalination Wind Turbine Model For Brackish Watermentioning
confidence: 99%
“…These systems, consist of the hydraulic pump in the nacelle, a variable displacement motor, and the electrical generator at the ground and other auxiliary components. The details of these systems are described in [13,14]. The main advantages are: …”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Professor Kong from Yanshan University, China, proposed a speed control for hydraulic wind turbines, established the hydraulic wind power equipment control model, and verified it experimentally [24]. In 2016, Zhang et al [29] further optimized the control model and obtained a more accurate and efficient control system. In 2014, the Energy Systems and Power Electronics Laboratory of the Indiana University--Purdue University Indianapolis (IUPUI) in the US constructed a hydraulic wind power system model that can resist fluctuations of high and low wind speeds by adjusting the simplified second-order model parameters [30].…”
Section: Development Of Hydraulic Wind Turbine Technologymentioning
confidence: 99%
“…They found that a hydraulic wind turbine has good performance under changing wind conditions. The authors in [11] have verified the mathematical model of a hydraulic wind turbine with MATLAB and AMESim. They have presented a control strategy to keep the motor speed constant.…”
Section: Introductionmentioning
confidence: 99%